The Kyoto Protocol: Is It Worth Reducing Our CO2 Emissions? (Observatorio Económico, 2013)
The Kyoto Protocol (1997) established a commitment by some developed countries to gradually reduce greenhouse gases. However, the United States and China, the countries that generate the most pollution, did not commit to reducing their emissions, which jeopardizes the entire future of the agreement. Why is international cooperation necessary, yet so difficult? Continue reading...
Keywords: Kyoto Protocol; Pollution; CO2